A case of “smoldering” immune‐mediated thrombotic thrombocytopenic purpura manifesting as recurrent cardioembolic stroke - Mark E. Pepin (Wiley, 2021)
Abstract Prompt recognition and treatment for thrombotic thrombocytopenic purpura (TTP) are critical to prevent the irreversible manifestations of this rare and quickly fatal hematologic disorder. Untreated TTP is typically a rapid‐onset disease with mortality exceeding 90% within days in the absence of appropriate treatment. In the current report, we describe a case of immune‐mediated TTP (iTTP) in a 62‐year‐old man manifesting as longstanding thrombocytopenia, recurrent cardioembolic strokes, and valvular thrombogenesis over a period of 3 years. We provide correlative evidence to support the potential contribution of adalimumab, a TNFα inhibitor, to the development of iTTP. We offer several educational insights regarding the identification of atypical presentations of iTTP owing to the longstanding disease course and numerous clinical comorbidities seen in this patient.